Orange-flesh sweet potato powder as a promising partial substitution rice flour to produce high quality and low glycemic index vermicelli - Tran Ngoc Giau; Hong Van Hao; Ngo Van Tai; Vo Quang Minh; Nguyen Minh Thuy (Journal of Agriculture and Food Research)
This study aims to improve the quality of vermicelli products by replacing a portion of rice flour with orange-fleshed sweet potato powder at four ratios ranging from 10 % (F1) to 25 % (F4) (5 % interval), while the control sample used 100 % rice flour (F0). The products were analyzed for quality and sensory characteristics. The analysis of five vermicelli production formulas revealed that the product made from formula F3, which contains OFSP powder and rice flour at a ratio of 20:80 %, had a relatively high amount of β-carotene (9.29 μg/g), a bright color (L∗ = 67.15, b∗ = 29.45), and a suitable hardness (46.79 g-force). The F3 sample had better cooking quality than the F0 sample, which was proved by the percentages of weight increase, volume increase, and dry matter loss of 59.88 %, 56.89 %, and 7.08 %, respectively. The estimated PRAL score of the product prepared from formula F3 was −1.45 (PRAL<0), indicating that the vermicelli product is alkaline, which can support and improve human health. A quantity of 100 g of vermicelli contains 25.15 g of carbohydrates, 3.17 g of protein, 1.48 g of lipids, 4.26 g of resistant starch, 2.43 g of fiber, and 1.66 g of ash. The reduction in estimated glycemic index (eGI) was also found, reaching a value of 51.24 for the F3 sample, whereas the eGI of F0 was 58.24 (medium-high range). Furthermore, microstructural image analysis (from a scanning electron microscope) of sample F3 indicated that OFSP powder addition could result in a better gel network structure than occurs in conventional vermicelli. The findings from this study will be a steppingstone to processing various popular food products with enhanced nutrients. This activity can also be developed on a larger production scale, improving the quality of life for communities, especially in areas with chronic vitamin A deficiency.